Effect of Seed Priming on Germination and Seedling Growth of Tomato (Solanum lycopersicum L. cv. Gaurabh 555) - Gyawali, Anisha; Bhusal, Babita; Bhandari, Nirajan; Lamsal, Ganesh (Journal of Agriculture and Forestry University, 2025)
Tomato (Solanum lycopersicum L.) is widely grown profitable vegetable in Nepal. However, low seed germination and poor seedling growth have been major constraints in tomato production. Seed priming as pre-sowing treatment enhances germination and produces uniform and vigorous seedlings that tolerate field stresses. An experiment was conducted in Gauradaha, Jhapa, Nepal during August-September, 2022 to evaluate the effect of seed priming on seed germination and seedling growth of tomato variety ‘Gaurabh 555’. This experiment was laid out in Completely Randomized Design (CRD) with eleven treatments and three replications including control, hydropriming (distilled water for 24 hours, hot water for 5 minutes), halopriming (potassium nitrate @ 0.25%, 0.5%, 0.75%, 1% for 24 hours) and hormonal priming (gibberellin @ 25 ppm , 50 ppm , 75 ppm , 100 ppm for 24 hours). Germination percentage, germination index and mean germination time were non-significant at 5% significance level but seedling growth parameters were significantly affected. The maximum shoot length (18.5 cm), root length (5.8 cm), number of leaves (5.2), seedling vigor index (2203), seedling fresh weight (1.16 g) and seedling dry weight (0.08 g) were observed in seeds primed with KNO3 @ 0.75%. Thus, KNO3 @ 0.75% enhanced the seedling growth, fresh and dry weight of tomato seedling under greenhouse conditions.